Effects of forest composition and disturbance on arbuscular mycorrhizae spore density, arbuscular mycorrhizae root colonization and soil carbon stocks in a dry afromontane forest in Northern Ethiopia - Birhane, Emiru; Gebretsadik, Kbrom Fissiha; Taye, Gebeyehu; Aynekulu, Ermias; Rannestad, Meley Mekonen; Norgrove, Lindsey (MDPI, 2020)
We investigated arbuscular mycorrhizal fungi (AMF) spore density and root colonization in three distinct dry Afromontane forest plant communities, representing differing levels of disturbance and soil properties. Soil and root samples were collected from sixty-five 50 × 50-m plots from four plant communities. We collected data for AMF spore density, AMF root colonization and soil organic carbon stocks in 0–25 and 25–50 cm soil depth ranges. AMF spore density, and root colonization differed significantly among plant communities. The least disturbed Juniperus procera– Maytenus senegalensis (Jupr-Mase) plant community, which contained high tree and shrub density, had the highest AMF spore density, root colonization and soil carbon stocks. The most disturbed Cadia purpurea–Opuntia ficus-indica (Capu-Opfi) community which contained the lowest tree and shrub density supported the lowest AMF spore density, root colonization and soil carbon stocks. There was no significant difference in spore density between the two soil depths, but AMF root colonization was significantly higher in the upper soil than in the subsoil (p < 0.001). The difference in soil properties was not uniform between plant communities. Conserving remnant dry Afromontane forests and restoring the degraded forests are critical to improve and maintain forest ecosystem functioning and sustain ecosystem services.